Proplyds in the flame nebula NGC 2024 - Haworth, Thomas; Kim, Jinyoung S; Winter, Andrew J.; Hines, Dean C; Clarke, Cathie J; Sellek, Andrew D; Ballabio, Giulia; Stapelfeldt, Karl R (Monthly notices of the Royal Astronomical Society, 2021)
A recent survey of the inner 0.35 × 0.35 pc of the NGC 2024 star-forming region revealed two distinct millimetre continuum disc populations that appear to be spatially segregated by the boundary of a dense cloud. The eastern (and more embedded) population is ∼0.2-0.5 Myr old, with an ALMA mm continuum disc detection rate of about $45\,$ per cent. However, this drops to only $\sim 15\,$ per cent in the 1-Myr western population. When these distinct populations were presented, it was suggested that the two main UV sources, IRS 1 (a B0.5V star in the western region) and IRS 2b (an O8V star in the eastern region, but embedded) have both been evaporating the discs in the depleted western population. In this paper, we report the firm discovery in archival HST data of four proplyds and four further candidate proplyds in NGC 2024, confirming that external photoevaporation of discs is occurring. However, the locations of these proplyds changes the picture. Only three of them are in the depleted western population and their evaporation is dominated by IRS 1, with no obvious impact from IRS 2b. The other five proplyds are in the younger eastern region and being evaporated by IRS 2b. We propose that both populations are subject to significant external photoevaporation, which happens throughout the region wherever discs are not sufficiently shielded by the interstellar medium. The external photoevaporation and severe depletion of mm grains in the 0.2-0.5 Myr eastern part of NGC 2024 would be in competition even with very early planet formation.